An environmentally friendly method of cutting and forming of materials by boron nitride coated tools. (1st January 2014) - Kaftanoğlu, Bilgin; Dökmetaş, Nihan
To decrease the undesirable effects on global warming and environmental pollution, manufacturing techniques should aim to use less energy, generate less pollution to the environment and aim at higher performance in shaping and cutting materials. In this paper, a new coating technique is presented for cutting and forming tools so that they can withstand higher temperatures, preserve their surface quality and cutting edge longer and require minimum quantity of lubrication (MQL) and achieve a longer life. It is known that coolants used in manufacturing cause environmental problems and their processing raises the manufacturing cost. Therefore, MQL or dry cutting is preferred if the tool material can withstand the high temperatures. A new technology of boron nitride (BN) coating using a physical vapour deposition (PVD) system is developed. BN coatings are applied on cutting tools and forming dies. Experiments and industrial applications show an increase in tool life. MQL and manufacturing at higher temperatures can be used due to the stability of BN.